Dívida pública e responsabilidade social do estado: recentralizando a dignidade da pessoa humana no orçamento público na busca pelo desenvolvimento - Menezes, Priscila Emanuele Falcão de Oliveira (2020)
The present work argues that the legal regulation of the Brazilian public debt is deficient and an obstacle for the country in adopting a developmental agenda regarding the fulfillment of international obligations in the matter of human rights. The beginning of the arguments starts from an introductory conceptual framework called public debt legal propaedeutics, where, from a transjuridic view, the concepts brought by the Brazilian financial doctrine and legislation to delimit the object of analysis of the research are presented. Then, the incompleteness of the legal treatment provided by the order for the control of public indebtedness and the need to know the composition of the national public debt stock is based, as the unconstitutional omission for the limitation of the federal public debt and the non-realization of the debt auditing (art. 26, of the Transitional Constitutional Provisions Act) prevent the necessary control actions so that the indebtedness process is a means of achieving economic growth capable of making the debt sustainable. The international panorama of the legal treatment of public debt is presented, based on the performance of organizations such as the United Nations, the Paris Club and the London Club. The principiological foundation is established from the idea of fiscal justice, sustainability and intergenerational responsibility from the perspective of the dignity of the human person and the main objectives of the Federative Republic of Brazil. Finally, it is concluded that from a human rights perspective, public debt management should consider public policies that enforce economic, social and cultural rights as a budget priority, committed to human development and reducing social inequality, based on theory of humanist capitalism and the proposal of the thesis defended here is that the national entities create a Social Responsibility Law, conditioning and holding the manager, during his financial-budgetary performance, to meet the minimum human development indices, as a precondition for the any public debt act, imposing sanctions along the same lines as the Fiscal Responsibility Law.